A combined dietary chronic toxicity and two-year carcinogenicity study of (2R, 4R)-monatin salt in Sprague–Dawley rats. (May 2016) - Brathwaite, Witty A.; Crincoli, Christine M.; Eapen, Alex K.; Rihner, Marisa O.; Nikiforov, Andrey I.; Remick, Amera K.
Abstract: In a combined chronic toxicity/carcinogenicity study, groups of Crl:CD(SD) rats were fed 0 (2 control groups), 5000, 20, 000, or 40, 000 ppm (2 R, 4 R )-monatin salt (hereafter " R, R -monatin") in the diet for up to one year in the chronic toxicity phase and up to two years in the carcinogenicity phase. There were no adverse effects on survival, incidence of palpable masses, neoplasms, organ weights, or ophthalmic examinations. The only notable effect was statistically significantly lower mean body weights and body weight gains in all treated groups generally throughout the study, which were most likely a result of caloric dilution of the test diets. Effects of long-term R, R -monatin ingestion by rats were predominantly focused on the urinary system ( i.e., clinical pathology alterations indicative of electrolyte and pH imbalances, increased incidence of renal calculi, mineralization and bone hyperostosis, and increased severity of chronic progressive nephropathy). The no-observed-adverse-effect level (NOAEL) for R, R -monatin from the chronic toxicity phase was 20, 000 ppm (equivalent to an exposure level of 1080 mg/kg bw/day for males and 1425 mg/kg/day for females) and from the carcinogenicity phase was 5000 ppm (equivalent to an exposure level of 238 and 302 mg/kg bw/day for males and females, respectively). Highlights: R, R- Monatin was tested in a combined one-year chronic toxicity and two-year carcinogenicity study in Sprague–Dawley rats. R, R- Monatin was offered ad libitum in the diet of Sprague–Dawley rats at 0, 5000, 20, 000, or 40, 000 ppm. Long-term ingestion of R, R- monatin (up to two years) resulted in significant effects predominantly on the urinary system. No evidence of carcinogenicity was detected in rats fed R, R- monatin in the diet for up to two years. The NOAEL was considered 20, 000 ppm for the chronic toxicity phase and 5000 ppm for the carcinogenicity phase.